(untitled) (World Bulletin of Management and Law, 2022)
Economic stability is a particularly rare socioeconomic phenomena. This is a pressing issue in the Agro-industrial Complex core, which is particularly vulnerable to external forces. On this basis, the paper investigates the peculiarities of food supply networks. Statistical indices of agricultural and agrarian food market sustainability in the Republic of Uzbekistan were examined, and conclusions were formed